Text and context in interpreting philosophical traditions: Global and islamic perspectives - Wahyuningsih Wahyuningsih (Islamic perspective on Communication and Psychology, 2025)
Background: The interpretation of texts in philosophical studies reflects an epistemological dynamic that extends beyond mere literal meaning, encompassing the historical, social, and cultural contexts in which texts are situated. This complexity underscores the evolving nature of textual meaning across different eras and intellectual traditions. Methods: This study employs a comparative approach to analyze interpretive methodologies within Western and Islamic schools of philosophy. It focuses on selected hermeneutical frameworks to explore how texts are reinterpreted in relation to changing historical and cultural contexts. Findings: In Western hermeneutics, approaches such as Gadamer’s fusion of horizons and Ricoeur’s narrative symbolism highlight the active interplay between the reader and the text. These perspectives emphasize meaning as a dialogical process shaped by both historical consciousness and linguistic structures. In contrast, the Islamic tradition offers interpretive models like Fazlur Rahman’s double movement, Abdullah Saeed’s contextual hermeneutics, and Mulla Sadra’s tafsir hikmah (philosophical exegesis), which strive to reinterpret revelation within the frameworks of modernity, spirituality, and rationality. These methods reflect an ongoing engagement with divine texts in light of contemporary challenges. Conclusion: The comparison reveals that both Western and Islamic philosophical traditions recognize the critical role of context in the process of textual interpretation. However, they are grounded in distinct theological assumptions and methodological orientations, which shape their respective hermeneutical outcomes. Novelty/Originality of this article: This study contributes to the field by bridging philosophical hermeneutics from two major intellectual traditions—Western and Islamic—demonstrating their convergences in contextual sensitivity while highlighting their foundational differences. It offers a nuanced understanding of how meaning is negotiated across cultural and religious boundaries.